Influence of UV-B radiation on Norway spruce seedlings (Picea abies (L.) Karst.) - Bavcon, Jože (Radiology and oncology (Ljubljana), 1998)
On the basis of the hypothesis that the ultraviolet radiation is one of the main causes for damage at higher altitudes, we have monitored the effect of UVradiation on Norway spruce for two and a half years. The influence of UV-B radiation on Picea abies (L). Karst.seedlings cultured in pots in open greenhouses was examined by measuring photochemical efficiency of photosystem II, changes in chlorophyll a, b, and changes in anthocyanins. The seedlings were grown in a mixture of peat and vermiculite (4:1). We used Osram ultravitaluks bulbs as a source of UV-B radiation. In the experiment plants were treated with 21.24+-3.5 kJ/m2 and 31.9+-2.5 KJ/m2. The control plants were grown under ambient conditions in the greenhouse without artificial source of UV-B radiation. The mean yearly values were as high as 11.5+-5.2 kJ/m2. The photochemical efficiency of photosystem II (PS II) in experimental plants did not vary during the experiment. It showed obvious decrease in the winter period, due to low temperatures and physical draught. The decrease in chlorophyll a and b, was already detected after one year of treatment with simultaneous changes in a/b ration. An increase of anthocyanins amount was detected as well.
Keywords: klorofil; radiacija; rastline; smreka; UV sevanje